OPTIMALISASI KINERJA TIM UNIT REAKSI CEPAT PENANGGANAN SAMPAH DALAM MENANGGULANGI SAMPAH LIAR DI WILAYAH II SUMEDANG KOTA PADA KABUPATEN SUMEDANG - Ningrum, Dhesti Widya Nurhasanah (LPPM UNSAP & FISIP UNSAP, 2024)
This study aims to analyze the optimization strategies of the Rapid Response Unit (URC) of the Environmental and Forestry Agency of Sumedang Regency in tackling illegal waste problems. The research design employed a qualitative method with data collected through observation, interviews, and documentation, while data analysis was carried out using data reduction, presentation, and conclusion drawing. The findings reveal that performance optimization is carried out through two main aspects: individual improvement and organizational environment enhancement. Individual improvement is realized through regular coaching, technical training, pre-work briefings, and recreational activities to maintain employee motivation and integrity. Meanwhile, organizational environment enhancement is achieved by providing adequate infrastructure, safety-standard work facilities, and strengthening work relations through coordination, communication, and consistent motivation. This study emphasizes that the integration of individual capacity building and organizational environment improvement significantly contributes to the effectiveness of the URC in handling illegal waste.